EXAMINING THE MUSEUM VISITORS USE OF MOBILE TECHNOLOGY THROUGH TECHNOLOGY ACCEPTANCE MODEL (TAM) - Nur Nabihah Mohamad Nizar; Mohd Khairezan Rahmat (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Museum is one of the educational centre for people to gain knowledge. Varieties of communication modes have been used to deliver the information to museum visitors. The advent of technology has brought to the usage of mobile technology in museum, thus ensure visitor’s meaningful experiences. Further, the integration of mobile technology in museum has facilitated visitor’s understanding of information about artefacts in the museum. In addressing this issue, the present study focused on factors that might influence museum visitors’ usage of mobile application based on the Technology Acceptance Model (TAM). Data for the study were collected through fifty-five responses from a survey questionnaire. All the museum visitors were asked to use their own mobile devices in order to access digital information provided in the museum. Findings show that perceived usefulness and perceived ease of use have directly influenced towards the actual use of mobile technology. The relationship between constructs is stronger mediated by attitude. Thus, museum visitors’ attitude has played an important role in determining the actual use of the mobile application.